Gender, Penerapan Kode Etik Profesi Akuntan dan Kualitas Penyusunan Anggaran Pendapatan dan Belanja Daerah - Prayudi, Made Aristia (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 12 No 2 (2017), 2017)
ABSTRACT The violation cases of codes of ethical conduct by professional accountants are rife in Indonesia. This phenomenon is expected to have negative impacts on the quality of government accountant. The purpose of this study areto investigate the influence of accountants’ codes of professional conduct implementation toward the quality of local government’s budget preparation; and todetermine whether or not there is a significant difference between male and female. This study is a quantitative research that employs survey method in which questionnaires are distributed to the financial officers of Finance and Asset Management Boardand Department of Revenue Service of Buleleng Regency in Bali. The data are analyzed usingSimple Linier Regression and Independent-Samples t-Test. Research findings indicate that accountants’ codes of professional conduct implementation have positive impact on the quality of local government’s budgetpreparation; and female government accountants are better than male on the implementation of accountants’ codes of professional conduct. Keywords:  Gender; implementation of accountants’ codes of professional conduct; quality of local government’s budget preparation; governmental Accounting
Keywords: Gender; Implementation of Accountants’ Codes of Professional Conduct; Quality of Local Government’s Budget Preparation; Governmental Accounting